Inclusion of cassava leaf meal for juvenile Nile tilapia - de Azevedo, Rafael Vieira; Ramos, Ana Paula de Souza; Carvalho, João Sérgio Oliveira; Braga, Luís Gustavo Tavares (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. de Azevedo R.V., Ramos A.P. de S, Carvalho J.S.O. & Braga L.G.T. [Inclusion of cassava leaf meal for juvenile Nile tilapia.] Inclusão do farelo da folha da mandioca para juvenis de tilápia do Nilo. Revista Brasileira de Medicina Veterinária 38(3):305-310, 2016. Instituto Capixaba de Pesquisa, Assistência Técnica e Extensão Rural, Av. Conde D’Eu 344, Centro, Ibiraçu, ES 29670-000, Brasil. E-mail: azevedorv84@gmail.com This work examined the performance, intestinal morphology and viability of including cassava leaf bran (CLB) in diets for Nile tilapia, Oreochromis niloticus. It was distributed 160 fish (41.30±1.46 g) into 20 hapas (0.60 x 0.50 x 0.30 m), installed within ten polyethylene tanks (310 L) in a completely randomized design with four treatments and five replications. The treatments consisted of a diet free of CLB and three diets with inclusion (10, 20 and 30%) of the CLB. Performance were evaluated as feed intake (FI), weight gain (WG), feed conversion rate (FCR) and survival (SUR). In morphometric analysis, was measured the height (HEI) and width of intestinal villi. For the economic analysis of diet were analyzed the cost of feed per kg weight gain (CFK) and economic efficiency index (EEI). Data were subjected to analysis of variance at 5% probability and polynomial regression. There were significant negative effects (P<0.05) of the inclusion of CLB on FI, WG and FCR, with increasing inclusion of CLB, does not influence (P>0.05) SUR. It was observed a significant effect (P<0.05) of level of inclusion of the CLB in the diet of tilapia on HEI, observing decreased linearly with increasing inclusion of CLB. It was observed that the inclusion of CLB increased significantly with increasing linear behavior, CFK, and hence worsened the EEI. It is concluded that the inclusion of the CLB is not feasible on the performance and economically, besides affecting the absorptive capacity of Nile tilapia, degraded performance.